2001
DOI: 10.1177/089686080102100108
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Residual Renal Function in Dialysis Patients: Effects of Dialysis-Technique–Related Factors

Abstract: Objectives Residual renal function (RRF) is of paramount importance to dialysis adequacy, morbidity, and mortality, particularly for long-term continuous ambulatory peritoneal dialysis (CAPD) patients. Residual renal function seems to be better preserved in patients on CAPD than in hemodialysis (HD) patients. We analyzed RRF in 45 patients with end-stage renal disease (ESRD), commencing either CAPD or HD, to prospectively define the time course of the decline in RRF, and to evaluate dialysis-technique–related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 15 publications
0
58
0
3
Order By: Relevance
“…better preservation of RKF with PD compared to HD. 75,76 Furthermore, the increasing use of frequent HD modalities, may accelerate loss of RKF. The Frequent Hemodialysis Network Nocturnal Trial that randomized patients to frequent 6X/week (nocturnal) or thrice-weekly in-center HD, frequent nocturnal HD was associated with a more rapid loss of RKF.…”
Section: Retrospective Studies By Misra Et Al and Lang Et Al Also Demmentioning
confidence: 99%
“…better preservation of RKF with PD compared to HD. 75,76 Furthermore, the increasing use of frequent HD modalities, may accelerate loss of RKF. The Frequent Hemodialysis Network Nocturnal Trial that randomized patients to frequent 6X/week (nocturnal) or thrice-weekly in-center HD, frequent nocturnal HD was associated with a more rapid loss of RKF.…”
Section: Retrospective Studies By Misra Et Al and Lang Et Al Also Demmentioning
confidence: 99%
“…43 Their results were subsequently duplicated by various authors (Table 1). [44][45][46][47][48][49] These studies all reported a significantly higher rate of decline of RRF in HD compared with PD patients. This was postulated to be due to improved cardiovascular stability with decreased hypotensive episodes in PD patients as a result of the continuous nature of the dialysis therapy, and/or the fact that the peritoneal membrane is more biocompatible than the membranes used in haemodialysers.…”
Section: Comparative Studies Of the Rate Of Decline Of Rrf Between Hdmentioning
confidence: 99%
“…Most, but not all recent studies ( Table 2) have reported that the use of biocompatible membranes such as polysulphone is associated with a slower rate of decline of RRF when compared with traditional bioincompatible cellulose membranes. 40,46,48,49,[53][54][55][56] The inflammatory milieu generated by the use of bioincompatible cellulose membranes is generally thought to be associated with a more rapid decline in RRF. 57,58 One limitation of these studies is the possible confounding factor of flux characteristics as the biocompatible synthetic membranes were largely high flux, while the bioincompatible membranes were low flux in nature.…”
Section: Does Biocompatibility Of Dialyser Membranes Affect the Rate mentioning
confidence: 99%
“…[37][38][39][40] Dialysis-related factors should be clearly identified and separated from the previous ones. 41 Few studies have attempted to identify precisely the role of the dialysis modality by itself. PD and HD and their related technical variants are the two main renal replacement options.…”
Section: Does Dialysis Modality Affect the Decline Of Rrf In Incidentmentioning
confidence: 99%